Evaluasi program sosialisasi vaksinasi covid-19 melalui media sosial - Aw, Suranto (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2021)
One of the evaluation parameters that can measure the effectiveness of socialization programs through social media is citizen engagement, namely public involvement in important or essential problems on social media. This evaluation was conducted to analyze the effectiveness of the Covid-19 vaccination socialization program through social media. The object of the evaluation is the netizen conversations on Twitter in the form of messages, statuses, or tweets that mention the keyword 'COVID-19 Vaccine' on social media. The effectiveness criteria of the socialization program were based on the citizen engagement index or the citizen involvement index which is examined from the netizen opinions on sentiment (positive/negative) and emotion (trust/fear) indicators. The evaluation results show that the socialization program has succeeded in increasing positive sentiment and emotions of trust. Positive sentiment was shown by netizens' opinions, which were dominated by posts that supported and accepted the vaccination program. Emotion of trust was dominated by the trust and acceptance posts. This finding, when confirmed with facts in the community, indicates a conformity. The public has supported, approved, trusted and accepted the Covid-19 vaccination.Salah satu parameter evaluasi yang dapat mengukur keefektifan program sosialisasi melalui media sosial  adalah citizen engagement, yaitu keterlibatan publik terhadap suatu problematika penting atau yang dianggap penting di media sosial. Evaluasi ini dilakukan untuk menganalisis keefektifan program sosialisasi vaksinasi Covid-19 melalui media sosial. Objek evaluasi adalah percakapan warganet di Twitter baik berupa pesan, status, maupun tweet yang menyebutkan kata kunci "˜Vaksin COVID-19' di media sosial. Kriteria keefektifan program sosialisasi mengacu kepada citizen engagement index atau indeks keterlibatan warganet yang dianalisis dari opini warganet pada indikator sentimen (positif/negative) dan emosi (trust/fear). Hasil evaluasi menunjukkan Program sosialisasi berhasil meningkatkan sentiment positif dan emosi trust. Sentimen positif ditunjukkan opini warganet yang didominasi unggahan mendukung dan menyetujui vaksinasi. Emosi trust, didominasi oleh unggahan rasa percaya dan menerima. Temuan ini apabila dikonfirmasi dengan fakta di masyarakat, mengindikasikan adanya kesesuaian. Masyarakat telah mendukung, menyetujui, percaya, dan menerima vaksinasi Covid-19.